2012
DOI: 10.3109/03009734.2011.641609
|View full text |Cite
|
Sign up to set email alerts
|

Substrate reduction therapy with miglustat for type 1 Gaucher disease: A retrospective analysis from a single institution

Abstract: Introduction. Gaucher disease (GD) is an infrequent progressive multisystem lysosomal storage disorder caused by the deficient activity of the lysosomal enzyme, glucocerebrosidase. A retrospective, single-center analysis of the clinical experience concerning the use of miglustat (N-butyldeoxynojirimycin), an oral inhibitor of glucosylceramide synthase, in type 1 Gaucher disease (GD1) was conducted to evaluate the efficacy, adverse events (AE), and outcome of miglustat therapy.Patients and methods. Six adult Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
7

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
0
18
0
7
Order By: Relevance
“…Since it slows down the production of glycosphingolipids, it should be effective in reducing storage of these compounds. Although positive effects of such treatment in clinical trials were reported (Elstein et al 2004;Pastores et al 2005), its efficacy in Gaucher disease has recently been questioned (Tylki-Szymanska et al 2011;Machaczka et al 2012).…”
Section: Substrate Reduction Therapies (Srps) For Mpsmentioning
confidence: 99%
“…Since it slows down the production of glycosphingolipids, it should be effective in reducing storage of these compounds. Although positive effects of such treatment in clinical trials were reported (Elstein et al 2004;Pastores et al 2005), its efficacy in Gaucher disease has recently been questioned (Tylki-Szymanska et al 2011;Machaczka et al 2012).…”
Section: Substrate Reduction Therapies (Srps) For Mpsmentioning
confidence: 99%
“…W Szwecji, liczącej niespełna 10 milionów mieszkańców, częstość występowania choroby Gauchera wynosi ok. 1:170 000 mieszkańców, lecz w pozostałych krajach nordyckich (Dania, Norwegia, Finlandia) jest ona niższa (ok. 1:420 000 mieszkańców) [26]. Co ciekawe, jak dotąd nie stwierdzono przypadku choroby Gauchera na Islandii.…”
Section: Rozprzestrzenienie Choroby Gaucheraunclassified
“…All patients also demonstrated increased plasma chitotriosidase activity. Both enzymes were assessed by a reference laboratory according to standard practice [6,19]. Further, direct DNA sequencing performed at the Academic Medical Centre in Amsterdam, Netherlands, revealed mutations in the GBA1 gene in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…GD1 is a slowly progressive illness, and clinical picture can vary from severe, lethal cases diagnosed in early childhood to completely asymptomatic patients [13][14][15][16]. Currently, GD is treatable and in the European Union there are two treatment options available for patients: (1) enzyme replacement therapy (ERT) with macrophage-targeted recombinant glucocerebrosidase (Cerezyme ® , Genzyme Corporation, Cambridge, MA, USA; VPRIV ® , Shire HGT, Lexington, MA, USA), and (2) substrate reduction therapy (SRT) with miglustat/N-butyldeoxynojirimycin (Zavesca ® , Actelion Pharmaceuticals, Allschwil, Switzerland) [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%